Incentives, Teachers, and Gender at Work - Robert, Sarah A. (Education Policy Analysis Archives, 2013)
Incentive pay programs have become panacea for a multitude of educational challenges. When aimed at teachers the assumption is that rewards entice them to work in particular ways or particular schools. However, the assumption is based on an economic formula that does not take into consideration the gendered nature of policy processes. This study examined ethnographically 10 teachers’ decision-making processes regarding whether to take up The Rural Program [La Ruralidad] in the Province of Buenos Aires, Argentina, which rewarded qualified educators with bonus pay to work in hard-to-staff schools, to address the question: How does gender mediate teachers’ decision-making process to take up an incentive reward? I isolate three conditions: safety, transportation, and community, to show how gendered relations, identities, and roles incentivize teachers. I argue that masculinities and femininities mediated teachers’ approach to taking up incentives. Rather than a simplistic, one-time-only decision, the study shows an on-going policy process that involves women and men in “rational economic decision making” mired by gender.